2004
DOI: 10.1128/aem.70.10.5744-5749.2004
|View full text |Cite
|
Sign up to set email alerts
|

Ferrihydrite-Dependent Growth of Sulfurospirillum deleyianum through Electron Transfer via Sulfur Cycling

Abstract: Observations in enrichment cultures of ferric iron-reducing bacteria indicated that ferrihydrite was reduced to ferrous iron minerals via sulfur cycling with sulfide as the reductant. Ferric iron reduction via sulfur cycling was investigated in more detail with Sulfurospirillum deleyianum, which can utilize sulfur or thiosulfate as an electron acceptor. In the presence of cysteine (0.5 or 2 mM) as the sole sulfur source, no (microbial) reduction of ferrihydrite or ferric citrate was observed, indicating that S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 22 publications
4
90
1
Order By: Relevance
“…Moreover, a single sulfate-reducing bacterium related to Desulfocapsa was reported to anaerobically utilize toluene with sulfate as the electron acceptor (Meckenstock, 1999;Winderl et al, 2007). Whether the observed Desulfobulbaceae in our enrichment were directly reducing ferric iron, or shuttling electrons for example via a sulfide/sulfur shuttle (Straub and Schink, 2004) cannot be discerned with the present results. Although sulfate was not present in our enrichment, another option (although unlikely) might be that sulfate reducers in our enrichment utilized oxidized sulfur species that were generated by oxygen seeping through the stopper.…”
Section: Desulfitobacterium Chlororespirans (T) U68528 Desulfosporoscontrasting
confidence: 53%
See 1 more Smart Citation
“…Moreover, a single sulfate-reducing bacterium related to Desulfocapsa was reported to anaerobically utilize toluene with sulfate as the electron acceptor (Meckenstock, 1999;Winderl et al, 2007). Whether the observed Desulfobulbaceae in our enrichment were directly reducing ferric iron, or shuttling electrons for example via a sulfide/sulfur shuttle (Straub and Schink, 2004) cannot be discerned with the present results. Although sulfate was not present in our enrichment, another option (although unlikely) might be that sulfate reducers in our enrichment utilized oxidized sulfur species that were generated by oxygen seeping through the stopper.…”
Section: Desulfitobacterium Chlororespirans (T) U68528 Desulfosporoscontrasting
confidence: 53%
“…As hypothesized above, they could then pass on part of the electrons to ferric iron either directly or indirectly via a sulfide/sulfur shuttle (Straub and Schink, 2004). It is important to note that the culture is not able to grow with benzene and sulfate as electron donor and acceptor.…”
Section: Syntrophic Interactions In Benzene Degradation Under Iron Rementioning
confidence: 99%
“…Redox coupling between sulfur and iron resulting in the recycling of sulfur has been previously demonstrated. For example, microbial studies in terrestrial environments illustrated that ferrihydrite can be reduced to ferrous iron through sulfur cycling with intermediate sulfur compounds like thiosulfate and elemental sulfur as the primary reductant (74,75). These authors also suggested that extremely insoluble iron minerals at ocean Eh-pH could be reduced through similar electron shuttling by intermediate valence state sulfur species.…”
Section: Discussionmentioning
confidence: 88%
“…In addition to organic heterocyclic and monocyclic compounds, sulfur species and hydrogen can be used as electron shuttles (Lovley, 2000;Straub and Schink, 2004;Niessen et al, 2005;Rabaey et al, 2006). To mimic the microbial shuttling, redox-active compounds such as neutral red can be added to the anode compartment of an MFC (Park and Zeikus, 2000).…”
Section: Electron Transfer Through Mobile Componentsmentioning
confidence: 99%